2004
DOI: 10.1002/marc.200400254
|View full text |Cite
|
Sign up to set email alerts
|

High‐Density Polyethylene Micro‐ and Nanocomposites: Effect of Particle Shape, Size and Surface Treatment on Polymer Crystallinity and Gas Permeability

Abstract: Summary: High‐density polyethylene (HDPE) micro‐ and nanocomposites with spherical and platelike inclusions were prepared and the effect of filler particles on polymer crystallinity and gas permeability was investigated. Platelike inclusions strongly reduce the polymer permeability coefficient, while spherical ones have no influence on it, irrespective of their size. The reduction in gas permeability depends on the average aspect ratio of the inclusions, which in turn depends on the exfoliation of the organo‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
56
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 23 publications
4
56
0
Order By: Relevance
“…The geometrical shape of the particle plays an important role in determining the properties of the composites [10]. There is 40% reduction in oxygen permeability upon the incorporation of 4%·vol organoclay into polyethylene, as reported by Osman et al [8,9]. Avella et al suggested that the calcium carbonate nanoparticles drastically reduced the permeability of oxygen and carbon dioxide for PP nanocomposites [11].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The geometrical shape of the particle plays an important role in determining the properties of the composites [10]. There is 40% reduction in oxygen permeability upon the incorporation of 4%·vol organoclay into polyethylene, as reported by Osman et al [8,9]. Avella et al suggested that the calcium carbonate nanoparticles drastically reduced the permeability of oxygen and carbon dioxide for PP nanocomposites [11].…”
Section: Introductionmentioning
confidence: 87%
“…Many studies have demonstrated improvements in permeability reduction to gases, moisture and organic vapours resulting from the addition of low concentrations of layered clay nanoparticles to various thermoplastic matrices [6][7][8]. Nanoparticles have been shown to influence the properties of the polymers at low volume fractions [9]. This is mainly due to their nanometer scale particle size and intraparticle distances.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of attention has been particularly paid these last years on nanofillers such as clays to reinforce PA or PE properties [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Indeed due to their high aspect ratio and their impermeable character, the clay platelets are expected to induce significant tortuosity effects when they are dispersed within a polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In the first case the nanoparticles are assumed to act as obstacles impeding the permeation of gas molecules through the film. [3][4][5][6][7][8][9] On the other hand, nanocomposite gas separation membranes have been described in which the nanoparticles seemed to enhance the gas transport properties of the film relative to the corresponding pure matrix material. [2,[10][11][12][13][14][15] Such contradictory results show that a simple and generalizing explanation for the influence of nanoparticles on the permeability of composite materials cannot be given.…”
Section: Introductionmentioning
confidence: 99%
“…[4,6] In case of an aspect ratio a of 1 (i.e., the particle shape is spherical) the Nielson equation is equal to the Maxwell equation described above. In many cases the obstacle models are not applicable, because they neglect possible interactions between nanoparticle and polymer as well as nanoparticle and penetrating gas molecules.…”
Section: Introductionmentioning
confidence: 99%